SYSTEMIC FUNCTIONAL LINGUISTIC GENRE PEDAGOGY (SFL GP) IN A TERTIARY EFL WRITING CONTEXT IN INDONESIA - Emilia, Emi; Hamied, Fuad Abdul (TEFLIN Journal, 2015)
This article reports on the results of a study aiming to investigate whether systemic functional linguistic genre pedagogy (SFL GP) can help students develop their writing ability in English and the students' opinions about the teaching program using SFL GP. The study was conducted in one semester with 19 student teachers taking a writing course on argumentative texts, in the English Department at a state university in West Java, Indonesia. The texts in focus were Exposition, Discussion and Response to Literary Works, but in the interests of space, the article will centre around Exposition. The study used a qualitative case study research design with data collected from participant observations for 16 meetings, analysis of students' texts collected over the program, and questionnaires distributed at the conclusion of the program. The results indicate that despite some aspects that still need improvement, SFL GP can generally help students develop their writing ability. Observation data show students' writing skill improvement supported by students' texts which depicts good control of the schematic structure and linguistic features of the texts in focus. Finally, questionnaire data reveal students' consciousness of improved writing skill and positive responses to each activity in the program. Based on the results of the study, it is recommended that SFL GP be implemented in other contexts in Indonesia and other countries.